Feasibility and Acceptability of Health Communication Interventions Within a Combination Intervention Strategy for Improving Linkage and Retention in HIV Care in Mozambique. (1st January 2017) - Sutton, Roberta; Lahuerta, Maria; Abacassamo, Fatima; Ahoua, Laurence; Tomo, Maria; Lamb, Matthew R.; Elul, Batya
Abstract : Background: Challenges to ensuring timely linkage to and retention in HIV care are well documented. Combination intervention strategies can be effective in improving the HIV care continuum. Data on feasibility and acceptability of intervention types within intervention packages are limited. Methods: The Engage4Health study assessed the effectiveness of a combination intervention strategy to increase linkage and retention among adults newly diagnosed with HIV in Mozambique. The study included 2 health communication interventions—modified delivery of pre-antiretroviral therapy (pre-ART) counseling sessions and SMS reminders—and 3 structural interventions—point-of-care CD4 testing after diagnosis, accelerated ART initiation, and noncash financial incentives. We used a process evaluation framework to assess dose delivered—extent each intervention was delivered as planned—and dose received—participant acceptability—of health communication versus structural interventions in the effectiveness study to understand associated benefits and challenges. Data sources included study records, participant interviews, and clinical data. Results: For dose delivered of health communication interventions, 98% of eligible clients received pre-ART counseling and 90% of participants received at least one SMS reminder. For structural interventions, 74% of clients received CD4 testing and 53% of eligible participants initiated ART within 1 month. Challenges for structural interventions included facility-level barriers, staffing limitations, and machine malfunctions. For dose received, participants reported pre-ART counseling and CD4 testing as the most useful interventions for linkage and financial incentives as the least useful for linkage and retention. Discussion: Findings demonstrate that health communication interventions can be feasibly and acceptably integrated with structural interventions to create combination intervention strategies.